The Role of Smart Tourism Technologies (STT) in Enhancing Visitor Satisfaction: A Case Study of Bostanliq Tourism Zone (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
The rapid development of digital technologies has significantly transformed the tourism industry worldwide. Smart Tourism Technologies (STT) have emerged as essential tools for improving tourist experiences, enhancing destination management, and increasing visitor satisfaction. These technologies include mobile applications, digital navigation systems, online booking platforms, virtual guides, artificial intelligence, and smart information services. The Bostanliq tourism zone, one of the most attractive tourist destinations in Uzbekistan, has considerable potential for integrating smart tourism solutions. This study examines the role of Smart Tourism Technologies in enhancing visitor satisfaction within the Bostanliq tourism zone. The findings indicate that the implementation of digital tourism services improves accessibility, convenience, safety, and overall tourist experiences. The study also highlights the importance of technological innovation in promoting sustainable tourism development and strengthening the competitiveness of tourism destinations
Keywords: Smart Tourism Technologies; visitor satisfaction; digital tourism